The Potential of Home-based Cardiac Rehabilitation Via Telehealth in Patients with the Post- Acute Coronary Syndrome in Indonesia: A Literature Review Study - Lutfian Lutfian; Nur Rohmawati; Nila Uli Saadah (Universitas Nahdlatul Ulama Surabaya, 2022)
Patients with post-acute coronary syndrome (ACS) require cardiac rehabilitation. However, there were obstacles in in-hospital cardiac rehabilitation (IHCR), so that it impacts on recurrence and a decreased quality of life. This paper analyzes the potential of home-based cardiac rehabilitation (HBCR) via Telehealth in post-ACS patients in Indonesia. It was a literature review study. We used articles from electronic media through the keywords home-based cardiac rehabilitation, Telehealth, and acute coronary syndrome. Journals were obtained through search sites on Google Scholar, Science Direct, PubMed, and ProQuest. The identification criteria were using Indonesian and English with the year of publication from 2015 to 2020. Then, we analysed and synthesized eligible publications using the PRISMA method. Findings from eight journals showed that the most common barriers for patients in in-hospital cardiac rehabilitation were logistical barriers (distance, time, functional status) and the patient's insufficient knowledge regarding the importance of cardiac rehabilitation. HBCR is an implementation model that has the potential as an effective solution in overcoming logistical limitations between patients and doctors. Care providers in several developed countries have implemented HBCR. It significantly improved medication adherence, outcome, and safety profile in patients. Furthermore, virtual cardiac rehabilitation provided the same outcome and safety profile as IHCR. Indonesia needs to develop HBCR via Telehealth for secondary prevention management in patients after heart events, especially ACS. Developing Telehealth could reduce complications and recurrence, improve lifestyle and physical